2005
DOI: 10.1152/ajpregu.00435.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glial-specific ablation of angiotensinogen lowers arterial pressure in renin and angiotensinogen transgenic mice

Abstract: -Angiotensinogen (AGT) is mainly expressed in glial cells in close proximity to renin-expressing neurons in the brain. We previously reported that glial-specific overexpression of ANG II results in mild hypertension. Here, we tested the hypothesis that glial-derived AGT plays an important role in blood pressure regulation in hypertensive mice carrying human renin (hREN) and human AGT transgenes under the control of their own endogenous promoters. To perform a glial-specific deletion of AGT, we used an AGT tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Both methods show that AGT is widely expressed in astrocytes (32,131), and in those cells, was localized in the nucleus (122). Genetic deletion of glial-specific AGT lowers arterial pressure in double transgenic mice expressing both human renin and human AGT (121), and antisense inhibition of glial AGT in rats results is altered baroreflex regulation and increased exercise tolerance (43,119). AGT is also expressed in neurons, specifically within nuclei of the brain important for cardiovascular (CV) regulation, such as the SFO, RVLM, PB, and PVN (58,136,150).…”
Section: Localization Of Ras Components Required For Ang II Productionmentioning
confidence: 99%
“…Both methods show that AGT is widely expressed in astrocytes (32,131), and in those cells, was localized in the nucleus (122). Genetic deletion of glial-specific AGT lowers arterial pressure in double transgenic mice expressing both human renin and human AGT (121), and antisense inhibition of glial AGT in rats results is altered baroreflex regulation and increased exercise tolerance (43,119). AGT is also expressed in neurons, specifically within nuclei of the brain important for cardiovascular (CV) regulation, such as the SFO, RVLM, PB, and PVN (58,136,150).…”
Section: Localization Of Ras Components Required For Ang II Productionmentioning
confidence: 99%
“…24,25 We showed that both glial and neuronal overexpression of renin and AGT leads to a modest elevation of blood pressure, and a glial-specific knockout of AGT in a model of systemic AGT overexpression with hypertension normalizes blood pressure. 26,27 Ang II has been postulated to act as a neurotransmitter and has been detected in nuclei, as well as in axonal projections between nuclei controlling cardiovascular function 28 (reviewed in Reference 29). One implication of the colocalization of renin, AGT, and Ang II is the potential for intracellular synthesis of Ang II.…”
Section: The Agt Gene and Proteinmentioning
confidence: 99%
“…However, RAS derived from glia seems to have a pivotal role in cardiovascular control by the central nervous system (Morimoto et al 2002;McKinley et al 2003;Sherrod et al 2005). Moreover, the differential modulation of baroreflex by neuron-and glia-derived Angiotensin II has been recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%